PVP-assisted Sb-doped SnO2 nanofibers synthesized by electrospinning process - Santibenchakul, Somtop; Chaiyasith, Suwan; Pecharapa, Wisanu (My University, 2016)
Well-defined Sb-doped tin oxide (ATO) nanofibers were synthesized by electrospinning technique. Polyvinylpyrrolidone (PVP), SnCl4·;5H2O and SbCl3 were chosen as suitable precursors for preparing ATO nanofibers. All of precursors were homogeneously dissolved with the mixture solvent of dimethylformamide (DMF) and absolute ethanol. Electrospinning process was carried out at applied voltage of 10 kV and distance between needle tip to aluminium foil collector was fixed at 10 cm. The injection rate of precursor solution was controlled at 0.5 ml/hr. The as-spun nanofibers were calcined at 600°C with heating rate of 5 °C/min in order to remove the PVP template and improve the crystallinity of ATO structure. Effect of Sb doping concentration on their crystal structure was investigated. The morphology and crystal structure of the electrospun fibers were analyzed by scanning electron microscope (SEM) and X-ray diffraction (XRD). In this work, the obtained ATO nanofibers had average range diameter from 150 to 350 nm with rough surface. Sb doping concentration in ATO nanofibers plays a key role on their network morphology. The excellent doping concentration of Sb that offered the continuous fibrous and porous ATO nanofibers was 7%.
Keywords: ATO nanofibers; Electrospinning; Polyvinylpyrrolidone (PVP)